PERBANDINGAN EFEKTIFITAS PENJUALAN MOBIL DAIHATSU MENGGUNAKAN MEDIA FACEBOOK DAN MEDIA BROSUR DI SANGATTA - Kasmiati; Nuuridha Matiin; Nurliati (Tinta Nusantara 2018 Vol.1, 2020)
This study aims to compare the effectiveness of selling Daihatsu cars using Facebook and brochure media. The research method used is a descriptive method using the EPIC dimension test and the difference test. The data collection instrument used a questionnaire with a sample of 60 Daihatsu Sangatta consumer respondents. From the results of the analysis of the discussion carried out by the author, the results of this study indicate that if Daihatsu car sales using Facebook media have an average score on a scale of 4.07, which means that sales effectiveness and effectiveness using brochures media have an average score on a scale of 4.06. which means it is effective and the results of the independent sample t-test (general difference test) with sig. (2-tailed) of 0.000 is smaller than the value of of 0.05.